PERBANDINGAN MODERNISASI PENDIDIKAN ISLAM MESIR DAN INDONESIA - FIHRIS KHOLIFATUL ALAM; ARIS EKO CAHYONO (Raudhah - Proud To Be Professional, 2022)
The development of Islamic education is not obtained by itself without contact with western countries. In classical history, it has been noted that the development of the Islamic world began with conflicts that occurred between Muslims and the western world, thus triggering the progress of the Islamic world. where the Muslim world wants to restore the glory of Islam again in this modern era after slumping for several centuries. Of course, Islamic educational institutions present an education system that produces students who have general knowledge and are supported by good religious knowledge. The emergence of the modernization of Islamic education in Egypt and Indonesia cannot be separated from the role of reformers who received enlightenment from the modernization movement in the field of education. As for modernization aspects that need to be considered in madrasas, among others are institutional development, more inclusive learning orientation of religious sciences, science learning general knowledge, and mindset changes to the demands of scientific progress.